ANALISIS PENGUASAAN KATA BANTU BILANGAN “CI”, “HUI”, “TANG” PADA MAHASISWA PENDIDIKAN BAHASA MANDARIN ANGKATAN 2016 FKIP UNIVERSITAS TANJUNGPURA - Elrisa Elrisa; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract“measure word” is one of sentence often using in Mandarin language and it is the important material in the teaching. For example the result of  complement words “ci”, “hui” and “tang” that always used in daily life. Seen from the understanding, they have similarities and differences of the meaning,so that the students make mistake when use them. To know how the mastery and difficulty level of the students Mandarin   education program’s in years 2016 FKIP of  Tanjungpura University.The writer conducted the test using questionnaire method to analyze of the students and the level difficulty using word“ci, hui, tang”. The results of the research show that there are part of the word have been mastered by the studenst and other part they can not mastery them. The correct percentage for the words “ci” is 73.06%, “hui” is 67.08%, “tang” is 62.22%.Keyword : “ci”, “hui” and “tang”, mastery analysis, The action-measure word